The Effectiveness of Straight Line Walk Application Used on Straight-Walking Skills for Blind Students - Dina Istiqomah Rahayu; Sunardi Sunardi (Journal of ICSAR, 2018)
Some studies explore the needs and problems in navigating on the blind person, the ability to walk in a straight line and avoid the tendency to veer. Difficulties that often occur from the tendency to turn is that when traveling straight on the road or open area where environmental information is not good enough to be considered a clue for the visually impaired to help them in maintaining a straight line route. The development of aids for the visually impaired in this era is growing rapidly, both tools to help navigate using global internet-based positioning system and tools to train straight walking using a compass-based system like straight line walks. The purpose of this research is to see the effectiveness of the straight line walk application for visually impaired students walking skills. This research is based on the absence of special attention from the school with the veering phenomenon that occurs in blind students, and its effect which endangers students (such as tripping, crashing into trees, and even walking towards the middle of the highway). This research used the experimental approach with SSR A-B design method. The results showed a decrease in turning distance on the three subjects after being given intervention by using the straight line walk application. Based on the results of this study, it can be concluded that the training program using the straight line walk application can improve the skills of walking straight on blind students.